High chlamydia positivity rates in Indigenous people attending Australian sexual health services. Issue 10 (2nd June 2014) - O'Connor, Catherine C; Ali, Hammad; Guy, Rebecca J; Templeton, David J; Fairley, Christopher K; Chen, Marcus Y; Dickson, Bridget M; Marshall, Lewis J; Grulich, Andrew E; Hellard, Margaret E; Kaldor, John M; Donovan, Basil; et al.
Abstract: Objective: To assess the clinical epidemiology of chlamydia among Aboriginal and Torres Strait Islander (Indigenous) people attending sexual health services around Australia. Design: Retrospective analysis of routine demographic, behavioural and clinical data, between 1 January 2006 and 31 December 2011. Setting: 18 sexual health services in major cities and regional centres in five jurisdictions. Main outcome measures: Attendance, chlamydia testing and positivity rates in patients visiting for the first time, and factors associated with chlamydia positivity. Results: Of 168 729 new patients, 7103 (4.2%) identified as Indigenous, of whom 74.3% were tested for chlamydia. Chlamydia positivity was 17.0% in Indigenous women (23.3% in 15–19‐year‐olds and 18.9% in 20–24‐year‐olds) and 17.3% in Indigenous men (20.2% in 15–19‐year‐olds and 24.2% in 20–24‐year‐olds). There was an increasing trend in chlamydia positivity in Indigenous women from 2006 to 2011 ( P for trend = 0.001), but not in Indigenous men. In Indigenous women, factors independently associated with positivity were: younger age, being heterosexual, living in Queensland and attending the service in 2010. In Indigenous men, independent factors associated with chlamydia positivity were younger age, being heterosexual, having sex only in Australia and living in a regional area. Conclusion: The high and increasing chlamydia positivity rates highlight the need for enhanced prevention and screening programs for Indigenous people.